Dispositivo para la estratificación de las propiedades visco-electro-elásticas de la piel - Lopez Jiménez, Daniel Alejandro; Flores Rodríguez, Enrique de José María; Hernandez Montelongo, Rosaura (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Objective: Measure the mechanical properties, galvanic response, and elasticity of the skin through the use of different techniques grouped in a multifunctional and wireless device. Results: The device built was able to collect, compute and send the data from the different sensors that make it up, to a database in Firebase for post-processing. Regarding the readings obtained, it can be observed that the height reached by the skin of the subjects has a considerably prolonged retraction time compared to the gradual decrease of the negative pressure in the indenter light, in addition, the electrical resistance does not seem to have a relationship with this phenomenon during this study, since this measurement is not very variable in each subject, but diverse among them. Conclusions: The data obtained show that the device is capable of measuring different height rates between subjects under the same environment, although all in different health conditions, so through this it is presumed that the properties of elasticity, electroconductivity and viscosity, among subjects with conditions of the integumentary tissue and thus create a pattern of their behavior, under the tests that appear in this work.